2013
DOI: 10.1016/j.jpor.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of stress relaxation in temporary and permanent luting cements

Abstract: The fractional stress loss could not be classified by the cement type. Two implant cements [Multilink Implant and IP Temp Cement] showed similar properties with permanent resin cements and temporary glass ionomer cements, respectively. Careful consideration of the choice of cement is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Ceramics including zirconia are brittle materials even though zirconia will achieve high strength due to transformation toughening; therefore, it was suggested that the luting cement will support the whole construction through its compression strength . The current study reported no fractured crowns along the follow‐up period in both study groups which indicates that luting cement has no effect on the fracture resistance of zirconia pediatric crowns.…”
Section: Discussionmentioning
confidence: 56%
“…Ceramics including zirconia are brittle materials even though zirconia will achieve high strength due to transformation toughening; therefore, it was suggested that the luting cement will support the whole construction through its compression strength . The current study reported no fractured crowns along the follow‐up period in both study groups which indicates that luting cement has no effect on the fracture resistance of zirconia pediatric crowns.…”
Section: Discussionmentioning
confidence: 56%
“…The manufacturer's product description declares TB to be a temporary cement, and in vitro studies show that the retentive properties of zinc oxide eugenol cement are less favorable than those of permanent cements. 35,36 However, these results apparently have no clinical relevance, as the loosening rate of suprastructures cemented with TB, for instance, is below that of suprastructures that are solely screw-retained. 5,37 Moreover, the product descriptions refer to tooth-supported suprastructures.…”
Section: Discussionmentioning
confidence: 99%
“…Its solubility in contact with liquid, thus avoiding remnants, as well as the antimicrobial properties of its components zinc oxide and eugenol make zinc oxide eugenol cement an ideal luting cement for dental restorations on implants, because high frequencies of peri‐implant mucositis are avoided. The manufacturer's product description declares TB to be a temporary cement, and in vitro studies show that the retentive properties of zinc oxide eugenol cement are less favorable than those of permanent cements . However, these results apparently have no clinical relevance, as the loosening rate of suprastructures cemented with TB, for instance, is below that of suprastructures that are solely screw‐retained .…”
Section: Discussionmentioning
confidence: 99%
“…ZOE cement (Temp‐Bond NX) is a temporary cement that has gained popularity due to easy manipulation, relatively low cost, and fractional stress relaxation . Stress releasing may be a good quality for cements used for implant prostheses, because implants lack the cushioning effect of the periodontal ligament, unlike natural teeth .…”
Section: Discussionmentioning
confidence: 99%
“…74 Stress releasing may be a good quality for cements used for implant prostheses, because implants lack the cushioning effect of the periodontal ligament, unlike natural teeth. 74 However, temporary cements show some disadvantages compared to permanent cements, such as more solubility, lower strength, easier debonding of the restoration, and radiolucent appearance in radiography. 24 Washout of temporary cements leads to a gap between restoration margin and the restoration margin that would result in tissue damage at the implant/tissue interface.…”
Section: Permanent Vs Temporary Cementationmentioning
confidence: 99%